Open Resource Binary & Interactive Technology (ORBIT): Platform Asset Digital untuk Diseminasi Karya Mahasiswa - Rickman Roedavan; Bambang Pudjoatmodjo; Yahdi Siradj (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Students in the Multimedia Engineering Technology Program (MET) at Telkom University possess the ability to create a diverse range of creative multimedia products, including 2D visual works, 3D modeling, and game applications. However, paradoxically, the documentation of their works often falls short, with their creations sporadically stored and inadequately cataloged. To address this challenge, we introduce Open Resource Binary & Interactive Technology (ORBIT), a digital asset platform designed to streamline the organization and management of multimedia projects generated by MET students. Through ORBIT, MET students can effortlessly upload, share, and document various types of multimedia projects, fostering collaboration among peers and ensuring that innovations in the multimedia field remain accessible and can be further developed by future generations